The consuming body - Falk, Pasi (Theory, culture & society (Unnumbered), 1994)
Pasi Falk offers a major synthesis and critical assessment of the debates surrounding the body, the self and contemporary consumer culture. He explores two fundamental issues for modern social theory - the delineation of modern consumption and the body's historically changing position in various cultural orders.